LOCALITY VALUE AS A REFLECTION OF CORE VALUES INCORPORATE CULTURE: A STUDY OF LOCAL ADVERTISING AGENCY (PETAKUMPET) - Agung Eko Budiwaspada; Fadillah Fadillah (Fakultas Seni Rupa dan Desain ITB, 2018)
Equivalent to the concept of culture in general, corporate culture is a value system that is believed, studied, applied, and developed by all individuals in the organization as a reference behavior to achieve corporate goals. If the agency's success is determined by its creativity in creating advertising idea, then the local advertising agency should have a chance to win the competition with a multinational advertising agency. To understand the existence of the local advertising agency creative ideas, the purpose of research is to understand the quality of creative ideas advertising messages by local advertising agencies as a modality for the competition in the globalization era and to gain an understanding of the reflection of corporate culture in local advertising agencies in order to identify the identity of Indonesian advertising. Using descriptive qualitative approach with semiotic analysis and content analysis, and choosing PT. Petakumpet as one of advertising agencies, this research showed that the reflection of core corporate culture values produces unique and distinctive indicators that refer to content in the vision and slogan, business environment, heroes, rituals and the network of advertising agency. The intensity of the reflection of each of the core values of corporate culture in the creative idea of advertising messages ultimately results in the characteristics that identify the advertisement of Petakumpet. Ads powered by high quality, creativity, and local generosity, will be able to penetrate beyond the local territory, in turn will become the identity of Indonesian advertising. At its peak, Indonesian ads will be able to compete globally.